PENGARUH PEMBERIAN EKSTRAK ETANOL DAUN KELOR (Moringa oleifera L.) TERHADAP AKTIVITAS ANALGESIK DAN ANTIINFLAMASI MELALUI EKSPRESI ENZIM SIKLOOKSIGENASE - Rini Sulistyawati; Pramita Yulli Pratiwi (Universitas Ahmad Dahlan, 2016)
Kelor (Moringa oleifera L.) contains flavonoid as a major of bioactive constituent. Quercetin as a flvonoid group inhibits COX-2 in inflammatory process. This study aimed to determine the effect of etanol extract of the kelor leaves on the analgesics and antiiinflamatory in mice. Etanol extract of the kelor leaves were evaluated for analgesics activity through writhing assay test at doses of 12.5; 25 and 50 mg/kgBW using Swiss albino mice. On the other hand antiinflammatory assay was performed by carrageenan induced paw edema of the etanol extract of the kelor leaves at 35; 70 and 140 mg/kgBW. Aspirin and sodiumdiclofenac were employeed as a standard for analgesic and antiinflammatory studies respectively. The result of the analysis show that etanol extract of the kelor leaves at doses 25 and 50 mg/kgBW decrease the number of writhing so that it have an analgesic power of 76.41±2.73% and 80.41±5.20%. Etanol extract of the kelor leaves at dosage 140 mg/kgBW show 24.30±2.960% antiinflammatory power and 46.37±6.434% on decreased COX-2 expression.